A scale dependent black hole in three-dimensional space–time. (25th October 2016) - Koch, Benjamin; Reyes, Ignacio A; Rincón, Ángel
Abstract: Scale dependence at the level of the effective action is a generic result of quantum field theory. Allowing for scale dependence of the gravitational couplings leads to a generalization of the corresponding field equations. In this work, those equations are solved by imposing the 'null energy condition' in three-dimensional space time with stationary spherical symmetry. The constants of integration are given in terms of the classical BTZ parameters plus one additional constant, that parametrizes the strength of the scale dependence. The properties such as asymptotics, horizon structure, and thermodynamics are discussed. It is found that the black hole entropy shows a remarkable transition from the usual 'area law' to an 'area × radius' law.